Strategi PT. Bluebrid Tbk dalam Menghadapi Persaingan Taksi Online Melalui Marketing Public Relations - Dwitia Masdarul Mawahib; Didik Hariyanto (Syntax Literate, 2023)
Online transportation has become a new alternative for people due to its efficiency and effectiveness. Some transportation services that have been around for a while have also transformed their booking systems to online platforms. One of the transportation companies that has revolutionized its booking process is PT. Blue Bird Tbk, which is still a popular choice among the public. Blue Bird is not just a company; it has become a lifestyle for many people. Although PT. Blue Bird Tbk does not offer motorbike services like PT. Go-Jek, PT. Grab, and MAXIM, its presence still poses competition for other online transportation services. In such a competitive landscape, companies need to establish a strong brand presence among the public. Marketing public relations play a crucial role in introducing the brand to the public. The focus of this research is PT. Blue Bird Tbk's strategy in dealing with the competition from online taxi services through marketing public relations. The research utilizes the theory of the PR marketing mix by Thomas L. Harris, which employs the concept of 'P.E.N.C.I.L.S.' This study adopts a qualitative research method with a descriptive case study approach, collecting data through interviews supplemented with additional data. Marketing public relations activities serve as marketing strategies through 7 PR marketing strategies, including publicity activities, creating engaging events, fostering good relationships with the community, establishing partnerships with other companies, building a positive image, and providing services with new features added to their network for the public. All of these are steps or strategies employed by PT. Blue Bird Tbk to provide the best service and strengthen brand awareness for PT. Blue Bird Tbk.